2009
DOI: 10.1029/2009jf001265
|View full text |Cite
|
Sign up to set email alerts
|

Rain splash of soil grains as a stochastic advection‐dispersion process, with implications for desert plant‐soil interactions and land‐surface evolution

Abstract: We formulate soil grain transport by rain splash as a stochastic advection‐dispersion process. By taking into account the intermittency of grain motions activated by raindrop impacts, the formulation indicates that gradients in raindrop intensity, and thus grain activity (the volume of grains in motion per unit area) can be as important as gradients in grain concentration and surface slope in effecting transport. This idea is confirmed by rain splash experiments and manifest in topographic roughening via mound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
124
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(128 citation statements)
references
References 49 publications
2
124
0
2
Order By: Relevance
“…According to this line of reasoning, plants can lead to the formation of mounds by trapping sediment and focusing aggradation (e.g., coppice dunes) or by locally inhibiting erosion and thereby forming mounds through the removal of material between patches of vegetation. Some Mima-like mounds may form through these processes (e.g., Furbish et al, 2009;Cramer and Barger, 2014), but several lines of observational evidence indicate that these mechanisms cannot explain the genesis of the mounds that we studied in the western U.S.…”
Section: Discussionmentioning
confidence: 93%
“…According to this line of reasoning, plants can lead to the formation of mounds by trapping sediment and focusing aggradation (e.g., coppice dunes) or by locally inhibiting erosion and thereby forming mounds through the removal of material between patches of vegetation. Some Mima-like mounds may form through these processes (e.g., Furbish et al, 2009;Cramer and Barger, 2014), but several lines of observational evidence indicate that these mechanisms cannot explain the genesis of the mounds that we studied in the western U.S.…”
Section: Discussionmentioning
confidence: 93%
“…5b). In addition to aeolian processes, the differential impact of rain-splash under variable canopy cover may influence tephra layer morphology at metre-scales11.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has demonstrated that vegetation structure can influence mean tephra layer thickness on a landscape scale111. Given that most land surfaces have some sort of vegetation cover, a greater understanding of the interaction between plants and tephra deposits would have global utility in the interpretation of tephra layers and their origins.…”
mentioning
confidence: 99%
“…The reason for such small drainages is an attempt to capture grus being detached from ridge crests, whether by raindrops (Furbish et al, 2009) or rain-impacted flow (Parsons et al, 1998), and then transported a few meters by the inter rill overland flow (Parsons et al, 1991). Field observations during intense rainstorms indicated that these traps captured grus detached by rainsplash and moved short distances by subsequent overland flow.…”
Section: Traps To Record Detachment Of Grusmentioning
confidence: 99%
“…Field observations during precipitation events indicate that short-distance transportation of a few meters or less occurred from inter rill flow after detachment (Parsons et al, 1991). Direct observations of detachment did not involve high-speed photography, and thus a determination could not be made whether ejection was from raindrops (Erpul et al, 2005;Furbish et al, 2009) or rain-impacted flow (Parsons et al, 1998). Table 2 Percent porosity of granitic materials in pits dug near sediment traps A1-7, B1-7, C1-7, and D1-7.…”
Section: Traps To Record Detachment Of Grusmentioning
confidence: 99%